Sexual risk reduction among Zambian couples - Ndashi Chitalu; Phillimon Ndubani; Miriam Mumbi; Deborah L Jones; Stephen M Weiss; Olga Villar-Loubet; Szonja Vamos; Drenna Waldrop-Valverde (Taylor & Francis Group, 2009)
Zambia has over 1 million HIV infections nationwide and an urban prevalence rate of 23%. This study compared the impact of male involvement in multiple and single session risk reduction interventions among inconsistent condom users in Zambia and the role of serostatus among HIV-seropositive and serodiscordant couples. Couples (N=392) were randomised into intervention arms. Among inconsistent condom users at baseline (N=83), condom use increased in both conditions and this increase was maintained over a 12-month period. At 12 months, seronegative men in the multiple session condition increased sexual barrier (male and female condoms) use in comparison with those in the single session condition (F=16.13, p=0.001) while seropositive individuals increased sexual barrier use regardless of condition. Results illustrate the importance of both single and multiple session risk reduction counselling among seronegative men in serodiscordant couples in Zambia, and highlight the differing perception of risk between seropositive and serodiscordant persons.